Healthcare provider person-centred practice: relationships between prerequisites, care environment and care processes using structural equation modelling - Nur Zahirah Balqis-Ali (BMC Health Services Research, 2022)
Abstract Background The translation of person-centred care concepts into practice requires fulfilment of necessary components, including person-centred values and practice held by the employees and having a supportive system. The objectives of this study were multifold: firstly, to evaluate the measurement model, secondly, to examine the roles of prerequisite or attributes of healthcare providers and care environment and how they affect delivery of person-centred processes; and finally, to examine the mediating effect of care environment towards the relationship between prerequisite and care processes. Methods A cross sectional study was conducted among healthcare providers working in primary care facilities in a state in Malaysia. The Person-centred Practice Inventory-Staff instrument (PCPI-S) was distributed and completed by respondents. The instrument structure, reliability and validity were assessed through confirmatory factor analysis, while the framework’s unidirectional hypothesis and the mediation path hypothesis were analysed using structural equation modelling. Results The overall goodness of fit verifies the original Person-centred Practice Framework, allowing some correlation errors. There were significant relationships between prerequisites of healthcare providers and care environment (β = 0.826, p < 0.001), as well as between care environment and care processes (β = 0.785, p < 0.001). This analysis also proved that care environment plays a partial mediating role in the relationship between prerequisites and care processes. Conclusions In order to successfully move towards delivering person-centred practice, it is imperative to equip healthcare providers with person-centred values and beliefs, while at the same time transform current work culture to align with person-centred care. This will allow successful delivery of person-centred processes. Trial registration NMRR-18-309-40,447.